Ultrahigh passive cooling power in hydrogel with rationally designed optofluidic properties - Fei, Jipeng (2024)
The cooling power of a radiative cooler is more than halved in the tropics, e.g., Singapore, because of its harsh weather conditions including high humidity (84% on average), strong downward atmospheric radiation (∼40% higher than elsewhere), abundant rainfall, and intense solar radiation (up to 1200 W/m2 with ∼58% higher UV irradiation). So far, there has been no report of daytime radiative cooling that well achieves effective subambient cooling. Herein, through integrated passive cooling strategies in a hydrogel with desirable optofluidic properties, we demonstrate stable subambient (4–8 °C) cooling even under the strongest solar radiation in Singapore. The integrated passive cooler achieves an ultrahigh cooling power of ∼350 W/m2, 6–10 times higher than a radiative cooler in a tropical climate. An in situ study of radiative cooling with various hydration levels and ambient humidity is conducted to understand the interaction between radiation and evaporative cooling. This work provides insights for the design of an integrated cooler for various climates.